2022
DOI: 10.1039/d2ra03944c
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic, cytotoxic and antioxidant activities of Rhodomyrtus tomentosa leaf extracts

Abstract: As part of our project on exploring Indonesian medicinal plants for antidiabetic and anticancer agents, this study was conducted to investigate the total phenolic and flavonoid contents, and antioxidant, cytotoxic and antidiabetic properties of R. tomentosa leaf extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In chronic lung disease patients, toxins and free radicals cause oxidative stress and lung tissue destruction. A quantitative UV-Vis spectrophotometer study found that the methanol fraction of Rhodomyrtus toementosa leaf methanol extract had the strongest antioxidant activity with an IC50 value of 51.95 g/mL ( Idris et al, 2022 ). Inflammation-induced oxidative stress may be caused by high IL-8 and insufficient glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…In chronic lung disease patients, toxins and free radicals cause oxidative stress and lung tissue destruction. A quantitative UV-Vis spectrophotometer study found that the methanol fraction of Rhodomyrtus toementosa leaf methanol extract had the strongest antioxidant activity with an IC50 value of 51.95 g/mL ( Idris et al, 2022 ). Inflammation-induced oxidative stress may be caused by high IL-8 and insufficient glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…Total phenolic content was determined based on the regular method applied in our laboratory 27 , 28 . The Modified Folin-Ciocalteu method was employed by mixing the sample (1000 ppm) with 10% Folin-Ciocalteu solution and 5% sodium carbonate.…”
Section: Methodsmentioning
confidence: 99%
“…Nasution et al (2015) [41] discovered that betasitosterol compounds derived from the bark of the A. camansi plant may decrease blood sugar levels in male Swiss Webster rats. Idris et al (2022) [42] discovered that methanol extract from the leaves of the Rhodomyrtus tomentosa plant has antidiabetic effects of 82.41 ± 2.21% against α-amylase inhibition and 81.91 ± 1.09% against αglucoamylase inhibition. Methanol extracts from the Allium consanguineum plant inhibited α-amylase at concentrations of 62.5, 125, 250, 500, and 1000 μg/mL, which was 29.88 ± 0.89%, 42.78 ± 0.45%, 47.44 ± 0.86%, 64.72 ± 0.89%, and 75.29 ± 0.64% [43].…”
Section: -5-antidiabetic Testmentioning
confidence: 99%